2015
DOI: 10.1016/j.ajo.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Adults With Strabismus

Abstract: Purpose To assess relative quality of life in patients with strabismus. Design Retrospective cohort study Methods The 25-item National Eye Institute Visual Functioning Questionnaire (NEI VFQ-25) was performed in 42 strabismic adults over the age of 50 years at a single institution. Subscale scores were compared with those of patients with other ocular diseases, including diabetic retinopathy, age-related macular degeneration (AMD), glaucoma, cataract, cytomegalovirus (CMV) retinitis, and low vision. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…In this cross-sectional study, the mean scores of all the NEI VFQ-25 subscales were lower in the low-vision group than in the control group (Table 2). Previously, Chang et al compared the NEI VFQ-25 scores among patients with various major ophthalmic diseases, such as low vision, strabismus, diabetic retinopathy, age-related macular degeneration, glaucoma, cataracts, and cytomegalovirus retinitis, and reported that the low-vision group had the lowest scores for most subscales, except for ocular pain [26]. It was obvious that low-vision patients experienced a lower VR-QoL than not only normal controls, but also other patients with ophthalmologic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-sectional study, the mean scores of all the NEI VFQ-25 subscales were lower in the low-vision group than in the control group (Table 2). Previously, Chang et al compared the NEI VFQ-25 scores among patients with various major ophthalmic diseases, such as low vision, strabismus, diabetic retinopathy, age-related macular degeneration, glaucoma, cataracts, and cytomegalovirus retinitis, and reported that the low-vision group had the lowest scores for most subscales, except for ocular pain [26]. It was obvious that low-vision patients experienced a lower VR-QoL than not only normal controls, but also other patients with ophthalmologic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…National Eye Institute Visual Function Questionnaire (NEI VFQ‐25) (Original [n = 7], Chinese [n = 4], German [n = 1])…”
Section: Resultsmentioning
confidence: 99%
“…The majority of individuals who suffer from strabismus report problems associated with double vision, motion detection, depth perception, balance, orientation and mobility. In particular by impacting appearance, strabismus has negative effects on not only self-image and self-esteem but also social prejudice that may affect career opportunities [16][17][18][19]. The main aim of strabismus management is to restore normal ocular alignment and reduce diplopia, if present, allowing the patient to carry out normal daily activities.…”
Section: Journal Of Patient Carementioning
confidence: 99%